Original articleAssociation of polymorphism 181 Ile/Leu of the high-affinity immunoglobulin E receptor beta chain gene with atopic dermatitis - Zabłotna, Monika; Nedoszytko, Bogusław; Wilkowska, Aleksandra; Gleń, Jolanta; Roszkiewicz, Jadwiga (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Genetic and environmental factors are known to play a role in the development of atopic dermatitis (AD). The high affinity receptor for IgE (FcεRI) is considered to play a main role in mast cell degranulation and IgE mediated allergy. Previous studies reported linkage between maternally inherited atopy and the gene of beta subunit of FcεRI located on chromosome 11q13. The aim of our study was to compare the frequency of occurrence of the polymorphic variants 181 Ile/Leu FcεRI-β between patients with AD and healthy members of their families. Using amplification refractory mutation system – polymerase chain reaction method (ARMS-PCR) we have analyzed polymorphism 181 Ile/Leu FcεRI in 172 members of 43 families with atopic dermatitis children. In the examined population there were 81 healthy persons and 91 persons with AD symptoms. The presence of Leu181 variant of FcεRI-β gene has been shown in 39 of 43 (90.7%) analyzed families. We have not found any differences in alleles and genotypes frequency of 181 Ile/Leu variants of FcεRI-β gene between AD and healthy members of the families. However, we have found that AD children more frequently inherited Leu181 variant from mother than from father. Our results indicate high frequency of Leu181 variant of FcεRI-β in families with atopic dermatitis children and suggest that variant Leu 181 within the FcεRI-β gene may be associated with maternally inherited AD.